GREEN ACCOUNTING HAS A POSITIVE IMPACT ON FINANCIAL PERFORMANCE, AND THIS IMPACT IS STRENGTHENED BY THE IMPLEMENTATION OF GCG - Wardayani Wardayani; Desy Irana Dewi Lubis (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Purpose:The existence of the Sei Mangkei Special Economic Zone (SEZ) actually has legitimacy in the community, but it still has an impact on environmental pollution, so a comprehensive improvement in environmental management is needed. The solution to this pollution can be realized by budgeting costs for environmental management or green accounting. Now, investors have consciously begun to add environmental aspects in determining investment instruments, so that Good Corporate Governance (GCG) is needed in its management. The implementation of GCG will have a positive impact on companies to encourage corporate concern for the surrounding environment. Method:The method used in this study is quantitative analysis, namely determining the influence of Green Accounting (Environmental Performance/X1 and Environmental Costs/X2) on Financial Performance (ROA and ROE/Y) and GCG (Z) moderating Green Accounting and Financial Performance. Findings:The study was conducted in companies already operating in the Sei Mangkei Special Economic Zone (SEZ) that have participated in the Company Performance Assessment Program (PROPER) issued by the Ministry of Environment and Forestry and include environmental costs. The data used are Financial Reports, Annual Reports, Sustainability Reports, and Company PROPER rating data. Partial Least Square (PLS)-SEM is the data analysis used with the help of SmartPLS software version 3.0. The results of this study are that Green accounting has a positive effect on financial performance, and this effect is strengthened by the implementation of GCG. Novelty: lies in its focus on companies operating in the Sei Mangkei Special Economic Zone (SEZ), a strategic industrial area in Indonesia that faces serious environmental challenges. Unlike previous research, green accounting is measured comprehensively through both environmental performance and environmental costs. Moreover, this study uniquely examines the moderating role of Good Corporate Governance (GCG), showing that governance practices strengthen the positive effect of green accounting on financial performance. Â Keywords: Accounting, Environment, Performance, Finance, GCG